TiCl4-Promoted Intramolecular Friedel–Crafts Cyclization of α-Keto-phenylbutanoates: Synthesis of Substituted Indane and Indene Derivatives - Ghosh, Arun K.; McDonald, Tristan John (Synlett, 2025)
We report a TiCl4-mediated intramolecular Friedel–Crafts type cyclization that provides convenient access to functionalized indane and indene derivatives. Reaction of α-ketoester derivatives bearing a phenylethyl side chain with 1.2 equiv of TiCl4 in CH2Cl2 at −78 °C provided indanyl α-hydroxy ester in good yield. However, the reaction at −78 to 23 °C furnished the corresponding elimination product, indene derivatives as a major product. Furthermore, the reaction of the keto ester with 1.2 equiv of TiCl4 at −78 to 23 °C afforded an interesting dimeric indanyl-indane derivative in good yield. Presumably, the dimerization reaction proceeds via TiCl4-mediated cationic intermediate.
Keywords: TiCl4; Friedel–Crafts; Cyclization; Indene derivatives; α-Keto esters; Cationic reaction